Astrocytes and Microglia as Potential Contributors to the Pathogenesis of C9orf72 Repeat Expansion-Associated FTLD and ALS - Rostalski, Hannah; Leskelä, Stina; Huber, Nadine; Katisko, Kasper; Cajanus, Antti; Solje, Eino; Marttinen, Mikael; Natunen, Teemu; Remes, Anne M.; Hiltunen, Mikko; Haapasalo, Annakaisa (Frontiers in Neuroscience, 2019)
Frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS) are neurodegenerative diseases with a complex, but often overlapping, genetic and pathobiological background and thus they are considered to form a disease spectrum. Although neurons are the principal cells affected in FTLD and ALS, increasing amount of evidence has recently proposed that other central nervous system-resident cells, including microglia and astrocytes, may also play roles in neurodegeneration in these diseases. Therefore, deciphering the mechanisms underlying the disease pathogenesis in different types of brain cells is fundamental in order to understand the etiology of these disorders. The major genetic cause of FTLD and ALS is a hexanucleotide repeat expansion (HRE) in the intronic region of the C9orf72 gene. In neurons, specific pathological hallmarks, including decreased expression of the C9orf72 RNA and proteins and generation of toxic RNA and protein species, and their downstream effects have been linked to C9orf72 HRE-associated FTLD and ALS. In contrast, it is still poorly known to which extent these pathological changes are presented in other brain cells. Here, we summarize the current literature on the potential role of astrocytes and microglia in C9orf72 HRE-linked FTLD and ALS and discuss their possible phenotypic alterations and neurotoxic mechanisms that may contribute to neurodegeneration in these diseases.